Manajemen koleksi museum dan problematika pengelolaannya di Kalimantan Selatan pada era new normal - Juairiah Juairiah (Perpustakaan Universitas Gadjah Mada, 2022)
Introduction. Museum collection management is interesting to discuss because it is one of the main activities in museum management as an information institution with problems, especially in the new normal era of famous museums in South Kalimantan (Lambung Mangkurat Museum, Wasaka Museum, and Sultan Suriansyah Museum). Research methods. This study uses a qualitative method by applying data collection techniques are: interviews, observations, and documents. Data Analysis. The data analysis process includes data reduction, data presentation, and conclusions/verification. Results and Discussion. In the new normal era, the Lambung Mangkurat Museum and Wasaka Museum have implemented the concept of museum collection management. In contrast, the Sultan Suriansyah Museum has not properly implemented the collection management concept. There were various problems in the management of museum collections and the solutions sought by each museum. Conclusions and Suggestions. Lambung Mangkurat Museum, Wasaka Museum, and the Sultan Suriansyah Museum continue to manage museum collections in the new normal era according to their capacity. Therefore, it is recommended that the government pay more attention to coaching and competency development for museum collection managers and the need for an e-catalog system in all museums.